Ten-Mile Morning: My Journey through Anorexia Nervosa - Lamparello, Adam (Hamilton Books, 2012)
Ten-Mile Morning is a true story about a man’s battle to overcome his five-year struggle with anorexia nervosa. Written from a painfully honest perspective, Adam Lamparello discusses his past addictions, depression, anxiety, and the emptiness that arose from his lack of self-esteem. This moving memoir details the author’s struggle to gain a sense of control and empowerment through dramatic weight loss, starvation, compulsive exercise, and purging. Ultimately, however, this is a story of hope and recovery. Ten-Mile Morning was written to inspire you and affirm that life after eating disorders is one of self-acceptance, self-respect, and most of all, one where you can achieve your dreams.